KINERJA APARATUR SIPIL NEGARA DALAM MELAKUKAN PELAYANAN PUBLIK PADA SEKRETARIAT DAERAH KABUPATEN KAMPAR BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Fatmawati, Fatmawati; Sutrisno, Hafiz; Firmanto, Fakhry (Jurnal Pahlawan, 2024)
ASN performance describes how far government organizations are able to achieve results when compared to the achievement of goals and targets that have been set. This study is a sociological legal study. The first research result is that employee performance in terms of Quantity, Quality and time is categorized as less good. Viewed from employee Work Behavior, in terms of integrity, commitment, and discipline, it is categorized as less good. In terms of service orientation, it has been categorized as good. Reliability and responsiveness are categorized as not good. Obstacles that occur in public services are the lack of quality human resources, undisciplined working conditions, and the lack of support factors from the government.   Keywords: ASN Performance, Public Services, Regional Secretariat